EVALUATION OF CROSS REACTIVITY BETWEEN Trypanosoma cruzi AND Leishmania infantum IN SEROLOGICALLY INELIGIBLE BLOOD DONORS DUE TO CHAGAS DISEASE - Maria Ferreira-Silva, Márcia; Fernando Guimarães Carvalho, Silvio; Fernandes Lula, Jamille; de Freitas Teles, Leandro; Valadares Basques, Fernando; Almeida Silva Teixeira, Luciana; Gomes Sales Tibúrcio, Monique; Moraes-Souza, Helio (Revista de Patologia Tropical / Journal of Tropical Pathology, 2017)
Inconclusive serological screening for Trypanosoma cruzi has been a problem for blood banks. This study examined the performance of serological techniques for Chagas disease in reagent samples from blood bank screenings and verified the possibilities of cross reactivity with visceral leishmaniasis. 68 samples of reagent donors tested with ELISA for Chagas disease were evaluated by other techniques and for the detection of anti-Leishmania antibodies. Four donors (5.9%) with positive results for T. cruzi were positive for ELISA Kalazar Detect (visceral leishmaniasis),three of which were confirmed by Western blot. This study confirms the specificity of the tests for Chagas disease in blood banks and reinforces the urgent adoption of measures to assess the real risk of transfusion transmission of visceral leishmaniasis.